Method for catalytically synthesizing antioxidant by adopting solid base

By using a supported solid alkali catalyst to carry out the transesterification reaction of antioxidant 1010, the problems of non-recyclable catalysts and equipment corrosion in the existing technology are solved, and an efficient and economical antioxidant synthesis process is realized.

CN119327510APending Publication Date: 2025-01-21ZHEJIANG DONGJIANG GREEN PETROCHEMICAL TECHNOLOGY INNOVATION CENTER CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411359831.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

In the preparation process of the existing antioxidant 1010, homogeneous catalysts have severe corrosion to the equipment and cannot be recycled, complicated post-treatment and poor economicality; organic tin catalysts are highly toxic, low reaction rate, high metal yield of product, and use Range is limited.

Method used

A solid alkali catalyst is used to synthesize antioxidant 1010. The solid alkali catalyst is a supported catalyst. Antioxidant 1010 is produced through a transesterification reaction. The catalyst can be recovered by simple filtration and washing, and remains relatively stable after repeated recycling. High catalytic activity.

Benefits of technology

It achieves high catalytic efficiency, convenient catalyst separation and recovery, and can still ensure high product yield after multiple recycling, reducing process complexity and economic costs.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of compound synthesis, and discloses a method for synthesizing an antioxidant through solid base catalysis, which comprises the following steps: carrying out ester exchange reaction on beta-(3, 5-di-tert-butyl-4-hydroxyphenyl) methyl propionate and pentaerythritol under the action of a solid base catalyst to obtain an antioxidant 1010; the preparation method of the solid base catalyst comprises the following steps: dispersing cellulose and carboxymethyl cellulose in water, adding a DMF solution of polyimide, mixing, adding PAE, and carrying out freeze molding and freeze drying; and immersing the obtained carrier in a mixed solution of ammonium polyphosphate and a metal salt solution, and then carrying out two-step calcination treatment to obtain the solid base catalyst. According to the invention, the heterogeneous solid base catalyst is used for catalytic synthesis of the antioxidant 1010, the product yield is high, and the catalyst still shows good catalytic activity after being recycled for many times.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of compound synthesis, in particular to a method for synthesizing an antioxidant by using solid base catalysis. Background Art

[0002] Pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (i.e. antioxidant 1010), white crystalline powder, has stable chemical properties. It can effectively prevent the thermal oxidation degradation of polymer materials during long-term aging. It is also a highly efficient processing stabilizer that can improve the discoloration resistance of polymer materials under high-temperature processing conditions. It is widely used in general-purpose plastics, engineering plastics, synthetic rubber, fibers, hot melt adhesives, resins, oils, inks, coatings, etc.

[0003] At present, the industrial production of antioxidant 1010 uses β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (i.e. 3,5-methyl ester) and pentaerythritol as raw materials, and is obtained through ester exchange reaction. One of the main differences in the process is the catalyst, which mainly includes strong bases (lithium acetate, sodium methoxide, potassium tert-butoxide, sodium hydroxide, etc.) and organic tin. The reason for choosing a strong base is that the stronger the alkalinity of the catalyst for the ester exchange reaction, the more conducive it is to the forward reaction. However, the traditional strong alkaline catalyst for the preparation of antioxidant 1010 is basically a homogeneous catalyst. Although the catalytic effect is good, the corrosion of the equipment is more serious, and it cannot be recycled, the post-processing is complicated, and the economic efficiency is poor. Organic tin catalysts are highly toxic, have a low reaction rate, and organic metals are difficult to remove. The metal yield of the product is high, and the scope of product use is limited.

[0004] The patent application with application number CN201611031948.9 discloses a method for preparing hindered phenol antioxidant 1010, which is prepared by transesterification reaction of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and pentaerythritol as raw materials, and uses alkaline ionic liquid as catalyst to accelerate the reaction. However, it is still a homogeneous reaction. Although the ionic liquid after the reaction can be separated by adding an external solvent, the preparation of the ionic liquid is cumbersome, and the post-reaction treatment needs to add solvent phase separation to separate the catalyst, making the process complicated and less economical.

[0005] The patent application with application number CN202311254369.0 discloses an antioxidant 1010 and its preparation method and application. The alkaline ionic liquid as the active component is loaded on a molecular sieve carrier, combined with a co-catalyst quaternary ammonium salt compound, quaternary phosphonium salt compound, phosphite compound or thioester compound, and a high yield of antioxidant 1010 can be obtained under the action of a solvent. Although the catalyst used in this patent can be easily separated, the system needs to add a co-catalyst, and the reaction needs to be heated multiple times, and the steps are cumbersome.

[0006] The patent application with application number CN202311406411.6 discloses a method for continuously preparing antioxidant 1010, in which two heterogeneous alkaline catalysts are prepared, one is a molecular sieve catalyst A loaded with ionic liquid, and the other is a molecular sieve catalyst B loaded with organic tin, and the two catalysts are added to two reactors connected in series respectively, and the raw material reacts with catalyst A and flows into the reactor containing catalyst B, thereby preparing antioxidant 1010. Although this method realizes continuous production, the operation is relatively cumbersome, and the product still contains some organic tin. Summary of the invention

[0007] In order to solve the above technical problems, the present invention provides a method for synthesizing an antioxidant using solid base catalysis. By using a solid base catalyst to catalyze the synthesis of antioxidant 1010, the catalytic efficiency is high and the catalyst separation and recovery are convenient. Moreover, the solid base catalyst is a supported catalyst, which can still ensure a high product yield after multiple recycling.

[0008] The purpose of the present invention is achieved through the following technical solutions: The invention provides a method for synthesizing an antioxidant by using solid base catalysis, comprising the following steps: subjecting β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and pentaerythritol to an ester exchange reaction under the action of a solid base catalyst to obtain an antioxidant 1010; wherein the preparation of the solid base catalyst comprises: dispersing cellulose and carboxymethyl cellulose in water, adding a DMF solution of polyimide to mix, then adding PAE to perform freeze molding and freeze drying; immersing the obtained carrier in a mixed solution of ammonium polyphosphate and a metal salt solution, wherein the metal element contained in the metal salt solution comprises K and at least one of Ca, Mg, Al, Zr and Sn, and then performing a two-step calcination treatment to obtain the solid base catalyst.

[0009] The present invention adopts a solid base catalyst to synthesize antioxidant 1010. The solid base catalyst is a heterogeneous catalyst, which can be simply separated after the transesterification reaction, and can be recycled and still have a good catalytic effect. Specifically, the cellulose and carboxymethyl cellulose in the solid base catalyst can be cross-linked under the action of the PAE wet strength agent to obtain a carrier with a certain strength, and the added polyimide can further improve the structural stability and thermal stability, ensuring that the catalyst has a high cyclic catalytic effect. After that, the carrier is loaded with metal cations. Since ammonium polyphosphate will form colloidal particles when added to water, and it can also chelate metal cations, it is helpful to load the metal cations on the porous carrier and can improve the loading binding effect. The loaded carrier is calcined in stages. During low-temperature calcination, ammonium polyphosphate will thermally decompose to generate gas, which is helpful to form porous structures and expose metal cations. Further high-temperature calcination will form a porous structure with more layers and increase the specific surface area. The polyimide and ammonium polyphosphate added to the carrier will work together with the metal elements to exert a better catalytic effect after calcination. At the same time, polyimide can enable the carrier to maintain high strength and structural integrity at high temperatures, and the recovery loss rate of the catalyst is low.

[0010] Preferably, the reaction temperature of the transesterification reaction is 170-200° C., the reaction time is 5-7 h, and the reaction pressure is -0.1 MPa.

[0011] Preferably, the amount of the solid base catalyst used is 1-3% of the mass of methyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate.

[0012] Preferably, the molar ratio of methyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate to pentaerythritol is 4.5-5:1.

[0013] Preferably, the mass concentration of the cellulose dispersed in water is 0.2-0.4%; the amount of the carboxymethyl cellulose is 20-30% of the mass of the cellulose; and the amount of the PAE is 20-30% of the mass of the cellulose.

[0014] The addition of carboxymethyl cellulose makes the combination compatibility between the cellulose matrix and the polyimide higher, and the stability of the carrier molding is improved through the entanglement and hydrogen bonding between the macromolecular chains, the cross-linking effect of the PAE wet strength agent, and freezing.

[0015] Preferably, the amount of the polyimide is 35-40% of the mass of the cellulose; the mass concentration of the DMF solution of the polyimide is 15-20%.

[0016] Preferably, the usage ratio of the carrier to the mixed solution is 1 g: 8-10 mL.

[0017] Preferably, the usage ratio of the ammonium polyphosphate to the metal salt solution is 15-20 g:1 L.

[0018] Preferably, the two-step calcination treatment is: first calcination treatment at 200-300°C for 30-100 min, and then calcination treatment at 500-700°C for 3-6 h.

[0019] Preferably, in the metal salt solution, the concentration of K is 0.25-0.3 mol / L, the total concentration of other metal elements is 0.4-0.6 mol / L, and the concentration of a single metal element is not less than 0.1 mol / L.

[0020] Preferably, the metal salt solution comprises one or more aqueous solutions of metal nitrates, metal carbonates, metal hydrochlorides and metal hydroxides.

[0021] Compared with the prior art, the present invention has the following beneficial effects: the present invention aims at the deficiencies of the prior art preparation technology of antioxidant 1010, uses a heterogeneous solid base catalyst to prepare and synthesize antioxidant 1010, and the solid catalyst can be recovered by simple filtering and washing, and the catalyst can be reused; and, the structure of the solid base catalyst is improved, and the loading firmness of the supported catalyst is improved, while the doped elements in the carrier will cooperate with the loaded metal elements to exert a better catalytic effect, so that the catalyst can still show good catalytic activity after multiple cycles. The present invention has a simple preparation process and good economic benefits. DETAILED DESCRIPTION

[0022] The technical solution of the present invention is described below with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0023] A method for synthesizing an antioxidant 1010 using solid base catalysis comprises the following steps: Step 1: Preparation of solid base catalyst: cellulose and carboxymethyl cellulose are dispersed in water, the mass concentration of cellulose dispersed in water is 0.2-0.4%, and then a DMF solution of polyimide with a mass concentration of 15-20% is added and stirred for 1-2 hours, and then a PAE wet strength agent is added and stirred for 3-5 hours, and the amount of carboxymethyl cellulose, polyimide and PAE is 20-30%, 35-40% and 20-30% of the mass of cellulose respectively; then freeze-molded at -10°C for 12-24 hours, and then freeze-dried at -20°C for 12-18 hours. Ammonium polyphosphate powder is gradually added into a metal salt solution and stirred, the dosage ratio of ammonium polyphosphate to the metal salt solution is 15-20 g / L, and a mixed solution is obtained; the formed carrier is immersed in the mixed solution, the dosage ratio of the carrier to the mixed solution is 1 g: 8-10 mL, and then calcined at 200-300° C. for 30-100 min, and then calcined at 500-700° C. for 3-6 h to obtain a solid base catalyst.

[0024] Step 2: conducting an ester exchange reaction between β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and pentaerythritol in a molar ratio of 4.5-5:1 under the action of a solid base catalyst at 170-200° C. and -0.1 MPa for 5-7 hours. The amount of the solid base catalyst used is 1-3% of the mass of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate to obtain antioxidant 1010.

[0025] In a specific embodiment of the present invention, cellulose is cellulose powder; carboxymethyl cellulose is carboxymethyl cellulose powder, 300-800 mPa·s; polyimide is soluble polyimide powder, with a glass transition temperature (Tg) of 320-330°C, a temperature of 5% thermal weight loss of about 525°C, and an intrinsic viscosity of 0.5-0.7 dl / g; PAE wet strength agent is the full name of polyamide polyepichlorohydrin resin, which is a water-soluble, cationic, thermosetting resin; ammonium polyphosphate is water-soluble ammonium polyphosphate, and the average degree of polymerization is 35-55.

[0026] In a specific embodiment of the present invention, the metal elements contained in the metal salt solution include metal A and metal B, metal A is K, and the concentration is 0.25-0.3 mol / L; metal B is at least one of Ca, Mg, Al, Zr, Sn, and the total metal concentration is 0.4-0.6 mol / L, and the concentration of a single metal element is not less than 0.1 mol / L.

[0027] In a specific embodiment of the present invention, the metal salt solution includes one or more aqueous solutions of metal nitrates, metal carbonates, metal hydrochlorides and metal hydroxides.

[0028] In a specific embodiment of the present invention, the temperature is first raised to 200-300°C at a heating rate of 3-5°C / min, and calcined for 30-100 minutes, and then raised to 500-700°C at a heating rate of 6-10°C / min, and calcined for 3-6 hours. Example 1 Step 1: Preparation of solid base catalyst: Disperse cellulose and carboxymethyl cellulose in water, the mass concentration of cellulose in water is 0.3%, then add DMF solution of polyimide with a mass concentration of 15% and stir and mix for 2 hours, then add PAE wet strength agent and stir and mix for 5 hours, the amount of carboxymethyl cellulose, polyimide and PAE is 27%, 38% and 25% of the mass of cellulose respectively; then freeze-form at -10℃ for 24 hours, and then freeze-dry at -20℃ for 16 hours. Add ammonium polyphosphate powder gradually into metal salt solution (metal salt solution is aqueous solution of K2CO3 and Al(NO3)3, K + The concentration is 0.25 mol / L, Al 3+ The concentration of the catalyst is 0.45 mol / L) and stirred, the amount ratio of ammonium polyphosphate to the metal salt solution is 16 g / L, and a mixed solution is obtained; the formed carrier is immersed in the mixed solution, the amount ratio of the carrier to the mixed solution is 1 g: 10 mL, then the temperature is increased to 250°C at a heating rate of 3°C / min, and the catalyst is calcined for 60 min, and then the temperature is increased to 600°C at a heating rate of 8°C / min, and the catalyst is calcined for 5 h to obtain a solid base catalyst.

[0029] Step 2: Carry out ester exchange reaction between β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and pentaerythritol in a molar ratio of 4.5:1 under the action of a solid base catalyst at 200°C and -0.1 MPa. The reaction time is 7 hours. The amount of the solid base catalyst used is 2% of the mass of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate to obtain antioxidant 1010.

[0030] Example 2 Step 1: Preparation of solid base catalyst: Disperse cellulose and carboxymethyl cellulose in water, the mass concentration of cellulose in water is 0.2%, then add DMF solution of polyimide with a mass concentration of 20% and stir and mix for 2 hours, then add PAE wet strength agent and stir and mix for 5 hours, the amount of carboxymethyl cellulose, polyimide and PAE is 30%, 36% and 28% of the mass of cellulose respectively; then freeze-form at -10℃ for 20 hours, and then freeze-dry at -20℃ for 18 hours. Add ammonium polyphosphate powder gradually into metal salt solution (metal salt solution is aqueous solution of K2CO3 and Al(NO3)3, K + The concentration is 0.30 mol / L, Al 3+The concentration of the catalyst is 0.40 mol / L) and stirred, the amount ratio of ammonium polyphosphate to the metal salt solution is 18 g / L, and a mixed solution is obtained; the formed carrier is immersed in the mixed solution, the amount ratio of the carrier to the mixed solution is 1 g: 10 mL, and then the temperature is increased to 250°C at a heating rate of 3°C / min, and the catalyst is calcined for 60 min, and then the temperature is increased to 600°C at a heating rate of 8°C / min, and the catalyst is calcined for 5 h to obtain a solid base catalyst.

[0031] Step 2: Carry out ester exchange reaction between β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and pentaerythritol in a molar ratio of 4.5:1 under the action of a solid base catalyst at 200°C and -0.1 MPa. The reaction time is 7 hours. The amount of the solid base catalyst used is 2% of the mass of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate to obtain antioxidant 1010.

[0032] Example 3 Step 1: Preparation of solid base catalyst: Disperse cellulose and carboxymethyl cellulose in water, the mass concentration of cellulose in water is 0.4%, then add DMF solution of polyimide with a mass concentration of 15% and stir and mix for 1 hour, then add PAE wet strength agent and stir and mix for 3 hours, the amount of carboxymethyl cellulose, polyimide and PAE is 20%, 40% and 25% of the mass of cellulose respectively; then freeze-form at -10℃ for 24 hours, and then freeze-dry at -20℃ for 16 hours. Add ammonium polyphosphate powder gradually into metal salt solution (metal salt solution is aqueous solution of K2CO3 and Al(NO3)3, K + The concentration is 0.25 mol / L, Al 3+ The concentration of the catalyst is 0.55 mol / L) and stirred, the amount ratio of ammonium polyphosphate to the metal salt solution is 20 g / L, and a mixed solution is obtained; the formed carrier is immersed in the mixed solution, the amount ratio of the carrier to the mixed solution is 1 g: 10 mL, and then the temperature is increased to 250°C at a heating rate of 3°C / min, and the catalyst is calcined for 60 min, and then the temperature is increased to 600°C at a heating rate of 8°C / min, and the catalyst is calcined for 5 h to obtain a solid base catalyst.

[0033] Step 2: Carry out ester exchange reaction between β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and pentaerythritol in a molar ratio of 4.5:1 under the action of a solid base catalyst at 200°C and -0.1 MPa. The reaction time is 7 hours. The amount of the solid base catalyst used is 2% of the mass of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate to obtain antioxidant 1010.

[0034] Example 4 The difference from Example 1 is that the metal salt solution is an aqueous solution of K2NO3 and Al(NO3)3.

[0035] Step 1: Preparation of solid base catalyst: Disperse cellulose and carboxymethyl cellulose in water, the mass concentration of cellulose in water is 0.3%, then add DMF solution of polyimide with a mass concentration of 15% and stir for 2 hours, then add PAE wet strength agent and stir for 5 hours, the amount of carboxymethyl cellulose, polyimide and PAE is 27%, 38% and 25% of the mass of cellulose respectively; then freeze-form at -10℃ for 24 hours, and then freeze-dry at -20℃ for 16 hours. Add ammonium polyphosphate powder gradually into metal salt solution (metal salt solution is aqueous solution of K2NO3 and Al(NO3)3, K + The concentration is 0.25 mol / L, Al 3+ The concentration of the catalyst is 0.45 mol / L) and stirred, the amount ratio of ammonium polyphosphate to the metal salt solution is 16 g / L, and a mixed solution is obtained; the formed carrier is immersed in the mixed solution, the amount ratio of the carrier to the mixed solution is 1 g: 10 mL, then the temperature is increased to 250°C at a heating rate of 3°C / min, and the catalyst is calcined for 60 min, and then the temperature is increased to 600°C at a heating rate of 8°C / min, and the catalyst is calcined for 5 h to obtain a solid base catalyst.

[0036] Example 5 The difference from Example 1 is that the metal salt solution is an aqueous solution of KF and Al(NO3)3.

[0037] Step 1: Preparation of solid base catalyst: Disperse cellulose and carboxymethyl cellulose in water, the mass concentration of cellulose in water is 0.3%, then add DMF solution of polyimide with a mass concentration of 15% and stir for 2 hours, then add PAE wet strength agent and stir for 5 hours, the amount of carboxymethyl cellulose, polyimide and PAE is 27%, 38% and 25% of the mass of cellulose respectively; then freeze-form at -10℃ for 24 hours, and then freeze-dry at -20℃ for 16 hours. Add ammonium polyphosphate powder gradually into metal salt solution (metal salt solution is aqueous solution of KF and Al(NO3)3, K + The concentration is 0.25 mol / L, Al 3+ The concentration of the catalyst is 0.45 mol / L) and stirred, the amount ratio of ammonium polyphosphate to the metal salt solution is 16 g / L, and a mixed solution is obtained; the formed carrier is immersed in the mixed solution, the amount ratio of the carrier to the mixed solution is 1 g: 10 mL, then the temperature is increased to 250°C at a heating rate of 3°C / min, and the catalyst is calcined for 60 min, and then the temperature is increased to 600°C at a heating rate of 8°C / min, and the catalyst is calcined for 5 h to obtain a solid base catalyst.

[0038] Example 6 The difference from Example 1 is that the metal salt solution is an aqueous solution of K2NO3 and ZrCl4.

[0039] Step 1: Preparation of solid base catalyst: Disperse cellulose and carboxymethyl cellulose in water, the mass concentration of cellulose in water is 0.3%, then add DMF solution of polyimide with a mass concentration of 15% and stir and mix for 2 hours, then add PAE wet strength agent and stir and mix for 5 hours, the amount of carboxymethyl cellulose, polyimide and PAE is 27%, 38% and 25% of the mass of cellulose respectively; then freeze-form at -10℃ for 24 hours, and then freeze-dry at -20℃ for 16 hours. Add ammonium polyphosphate powder gradually into metal salt solution (metal salt solution is aqueous solution of K2NO3 and ZrCl4, K + The concentration of Zr is 0.25mol / L. 4+ The concentration of the catalyst is 0.45 mol / L) and stirred, the amount ratio of ammonium polyphosphate to the metal salt solution is 16 g / L, and a mixed solution is obtained; the formed carrier is immersed in the mixed solution, the amount ratio of the carrier to the mixed solution is 1 g: 10 mL, then the temperature is increased to 250°C at a heating rate of 3°C / min, and the catalyst is calcined for 60 min, and then the temperature is increased to 600°C at a heating rate of 8°C / min, and the catalyst is calcined for 5 h to obtain a solid base catalyst.

[0040] Example 7 The difference from Example 1 is that the metal salt solution is an aqueous solution of KOH and SnCl4.

[0041] Step 1: Preparation of solid base catalyst: Disperse cellulose and carboxymethyl cellulose in water, the mass concentration of cellulose in water is 0.3%, then add DMF solution of polyimide with a mass concentration of 15% and stir and mix for 2 hours, then add PAE wet strength agent and stir and mix for 5 hours, the amount of carboxymethyl cellulose, polyimide and PAE is 27%, 38% and 25% of the mass of cellulose respectively; then freeze-form at -10℃ for 24 hours, and then freeze-dry at -20℃ for 16 hours. Gradually add ammonium polyphosphate powder to metal salt solution (metal salt solution is aqueous solution of KOH and SnCl4, K + The concentration of Sn is 0.25mol / L, 4+ The concentration of the catalyst is 0.45 mol / L) and stirred, the amount ratio of ammonium polyphosphate to the metal salt solution is 16 g / L, and a mixed solution is obtained; the formed carrier is immersed in the mixed solution, the amount ratio of the carrier to the mixed solution is 1 g: 10 mL, then the temperature is increased to 250°C at a heating rate of 3°C / min, and the catalyst is calcined for 60 min, and then the temperature is increased to 600°C at a heating rate of 8°C / min, and the catalyst is calcined for 5 h to obtain a solid base catalyst.

[0042] Example 8 The difference from Example 1 is that the metal salt solution is an aqueous solution of KNO3 and Mg(OH)2.

[0043] Step 1: Preparation of solid base catalyst: Disperse cellulose and carboxymethyl cellulose in water, the mass concentration of cellulose in water is 0.3%, then add DMF solution of polyimide with a mass concentration of 15% and stir and mix for 2 hours, then add PAE wet strength agent and stir and mix for 5 hours, the amount of carboxymethyl cellulose, polyimide and PAE is 27%, 38% and 25% of the mass of cellulose respectively; then freeze-form at -10℃ for 24 hours, and then freeze-dry at -20℃ for 16 hours. Add ammonium polyphosphate powder gradually into metal salt solution (metal salt solution is aqueous solution of KNO3 and Mg(OH)2, K + The concentration is 0.25mol / L, Mg 2+ The concentration of the catalyst is 0.45 mol / L) and stirred, the amount ratio of ammonium polyphosphate to the metal salt solution is 16 g / L, and a mixed solution is obtained; the formed carrier is immersed in the mixed solution, the amount ratio of the carrier to the mixed solution is 1 g: 10 mL, and then the temperature is increased to 250°C at a heating rate of 3°C / min, and the catalyst is calcined for 60 min, and then the temperature is increased to 500°C at a heating rate of 8°C / min, and the catalyst is calcined for 6 h to obtain a solid base catalyst.

[0044] Example 9 The difference from Example 1 is that the metal salt solution is an aqueous solution of KNO3 and Ca(NO3)2.

[0045] Step 1: Preparation of solid base catalyst: Disperse cellulose and carboxymethyl cellulose in water, the mass concentration of cellulose in water is 0.3%, then add DMF solution of polyimide with a mass concentration of 15% and stir and mix for 2 hours, then add PAE wet strength agent and stir and mix for 5 hours, the amount of carboxymethyl cellulose, polyimide and PAE is 27%, 38% and 25% of the mass of cellulose respectively; then freeze-form at -10℃ for 24 hours, and then freeze-dry at -20℃ for 16 hours. Add ammonium polyphosphate powder gradually into metal salt solution (metal salt solution is aqueous solution of KNO3 and Ca(NO3)2, K + The concentration of Ca is 0.25 mol / L. 2+ The concentration of the catalyst is 0.45 mol / L) and stirred, the amount ratio of ammonium polyphosphate to the metal salt solution is 16 g / L, and a mixed solution is obtained; the formed carrier is immersed in the mixed solution, the amount ratio of the carrier to the mixed solution is 1 g: 10 mL, and then the temperature is increased to 250°C at a heating rate of 3°C / min, and the catalyst is calcined for 60 min, and then the temperature is increased to 500°C at a heating rate of 8°C / min, and the catalyst is calcined for 5 h to obtain a solid base catalyst.

[0046] Comparative Example 1 The difference from Example 1 is that the catalyst does not contain a carrier.

[0047] Step 1: Preparation of solid base catalyst: Weigh 41.5g KNO3 and 75g Al2O3, add to 100mL water, stir evenly, filter, and dry the solid in vacuum at 110°C. Grind the solid into powder, heat it to 600°C at a heating rate of 8°C / min and keep it for 5h, then cool it down for standby use to obtain a solid base catalyst.

[0048] Comparative Example 2 The difference from Example 1 is that the metal salt solution does not contain K.

[0049] Step 1: Preparation of solid base catalyst: Disperse cellulose and carboxymethyl cellulose in water, the mass concentration of cellulose in water is 0.3%, then add DMF solution of polyimide with a mass concentration of 15% and stir for 2 hours, then add PAE wet strength agent and stir for 5 hours, the amount of carboxymethyl cellulose, polyimide and PAE is 27%, 38% and 25% of the mass of cellulose respectively; then freeze-form at -10℃ for 24 hours, and then freeze-dry at -20℃ for 16 hours. Add ammonium polyphosphate powder gradually into metal salt solution (metal salt solution is Al(NO3)3 aqueous solution, Al 3+ The concentration of the catalyst is 0.45 mol / L) and stirred, the amount ratio of ammonium polyphosphate to the metal salt solution is 16 g / L, and a mixed solution is obtained; the formed carrier is immersed in the mixed solution, the amount ratio of the carrier to the mixed solution is 1 g: 10 mL, then the temperature is increased to 250°C at a heating rate of 3°C / min, and the catalyst is calcined for 60 min, and then the temperature is increased to 600°C at a heating rate of 8°C / min, and the catalyst is calcined for 5 h to obtain a solid base catalyst.

[0050] Comparative Example 3 The difference from Example 1 is that no polyimide is added in the preparation of the catalyst.

[0051] Step 1: Preparation of solid base catalyst: Disperse cellulose and carboxymethyl cellulose in water, the mass concentration of cellulose in water is 0.3%, then add PAE wet strength agent and stir for 5 hours, the amount of carboxymethyl cellulose and PAE is 27% and 25% of the mass of cellulose respectively; then freeze-form at -10℃ for 24 hours, and then freeze-dry at -20℃ for 16 hours. Add ammonium polyphosphate powder gradually into metal salt solution (metal salt solution is aqueous solution of K2CO3 and Al(NO3)3, K + The concentration is 0.25 mol / L, Al 3+The concentration of the catalyst is 0.45 mol / L) and stirred, the amount ratio of ammonium polyphosphate to the metal salt solution is 16 g / L, and a mixed solution is obtained; the formed carrier is immersed in the mixed solution, the amount ratio of the carrier to the mixed solution is 1 g: 10 mL, then the temperature is increased to 250°C at a heating rate of 3°C / min, and the catalyst is calcined for 60 min, and then the temperature is increased to 600°C at a heating rate of 8°C / min, and the catalyst is calcined for 5 h to obtain a solid base catalyst.

[0052] Comparative Example 4 The difference from Example 1 is that ammonium polyphosphate is not added during the preparation of the catalyst.

[0053] Step 1: Preparation of solid base catalyst: Disperse cellulose and carboxymethyl cellulose in water, the mass concentration of cellulose in water is 0.3%, then add DMF solution of polyimide with a mass concentration of 15% and stir and mix for 2 hours, then add PAE wet strength agent and stir and mix for 5 hours, the amount of carboxymethyl cellulose, polyimide and PAE is 27%, 38% and 25% of the mass of cellulose respectively; then freeze-form at -10℃ for 24 hours, and then freeze-dry at -20℃ for 16 hours. Immerse the molded carrier in a metal salt solution (the metal salt solution is an aqueous solution of K2CO3 and Al(NO3)3, K + The concentration is 0.25 mol / L, Al 3+ The concentration of the catalyst is 0.45 mol / L), the ratio of the carrier to the metal salt solution is 1 g:10 mL, then the temperature is increased to 250°C at a heating rate of 3°C / min, and the catalyst is calcined for 60 min, and then the temperature is increased to 600°C at a heating rate of 8°C / min, and the catalyst is calcined for 5 h to obtain a solid base catalyst.

[0054] Comparative Example 5 The difference from Example 1 is that the catalyst is not subjected to calcination treatment at 250°C.

[0055] Step 1: Preparation of solid base catalyst: Disperse cellulose and carboxymethyl cellulose in water, the mass concentration of cellulose in water is 0.3%, then add DMF solution of polyimide with a mass concentration of 15% and stir and mix for 2 hours, then add PAE wet strength agent and stir and mix for 5 hours, the amount of carboxymethyl cellulose, polyimide and PAE is 27%, 38% and 25% of the mass of cellulose respectively; then freeze-form at -10℃ for 24 hours, and then freeze-dry at -20℃ for 16 hours. Add ammonium polyphosphate powder gradually into metal salt solution (metal salt solution is aqueous solution of K2CO3 and Al(NO3)3, K + The concentration is 0.25 mol / L, Al 3+The concentration of the catalyst is 0.45 mol / L) and stirred, the amount ratio of ammonium polyphosphate to the metal salt solution is 16 g / L, and a mixed solution is obtained; the formed carrier is immersed in the mixed solution, the amount ratio of the carrier to the mixed solution is 1 g: 10 mL, and then the temperature is increased to 600°C at a heating rate of 8°C / min, and the catalyst is calcined for 5 hours to obtain a solid base catalyst.

[0056] The yield of the target product tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid] pentaerythritol ester was shown by high performance liquid chromatography (HPLC) analysis, and the product color was pure white. The solid catalyst was washed with ethanol and then vacuum dried before being used in the next catalytic cycle, and then used in the preparation of antioxidant 1010 according to the above method, and the yield of the target product was measured again.

[0057] Table 1 Solid base catalyst Product yield / % Product yield after 5 cycles / % Example 1 <![CDATA[K2CO3 / Al(NO3)3 + carrier]]> 98.1 97.8 Example 2 <![CDATA[K2CO3 / Al(NO3)3 + carrier]]> 97.7 96.2 Example 3 <![CDATA[K2CO3 / Al(NO3)3 + carrier]]> 96.9 95.6 Example 4 <![CDATA[K2NO3 / Al(NO3)3 + carrier]]> 98.9 98.1 Example 5 <![CDATA[KF / Al(NO3)3 + support]]> 96.9 95.2 Example 6 <![CDATA[K2NO3 / ZrCl4 + support]]> 98.1 96.9 Example 7 <![CDATA[KOH / SnCl4 + support]]> 98.9 97.7 Example 8 <![CDATA[KNO3 / Mg(OH)2 + carrier]]> 98.5 97.6 Example 9 <![CDATA[KNO3 / Ca(NO3)2 + carrier]]> 99.2 98.3 Comparative Example 1 <![CDATA[K2CO3 / Al(NO3)3]]> 91.6 65.8 Comparative Example 2 <![CDATA[Al(NO3)3 + carrier]]> 95.1 92.7 Comparative Example 3 <![CDATA[K2CO3 / Al(NO3)3 + carrier]]> 97.6 89.9 Comparative Example 4 <![CDATA[K2CO3 / Al(NO3)3 + carrier]]> 92.3 77.8 Comparative Example 5 <![CDATA[K2CO3 / Al(NO3)3 + support]]> 97.0 90.5 As shown in Table 1, the solid base catalyst of the present invention is used to catalyze the synthesis of antioxidant 1010, and a higher product yield can be obtained, and a higher product yield can still be maintained after recycling 5 times. The solid base catalyst is a supported catalyst. Compared with Comparative Example 1 without adding a carrier, Examples 1-9 can all obtain higher product yields, indicating that the carrier helps the catalyst to obtain higher catalytic activity and structural stability. Comparative Examples 3-5 show that the preparation of the carrier will affect the catalyst structure, and then affect the catalytic effect of the catalyst. Comparative Example 2 shows that the combination of K element and carrier has a good synergistic effect, and can make the catalyst have a higher catalytic activity in the reaction of catalytic synthesis of antioxidant 1010.

[0058] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the specification of the present invention, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for synthesizing an antioxidant using solid base catalysis, characterized in that: The method comprises the following steps: subjecting β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and pentaerythritol to an ester exchange reaction under the action of a solid base catalyst to obtain an antioxidant 1010; wherein the preparation of the solid base catalyst comprises: dispersing cellulose and carboxymethyl cellulose in water, adding a DMF solution of polyimide to mix, then adding PAE to perform freeze molding and freeze drying; immersing the obtained carrier in a mixed solution of ammonium polyphosphate and a metal salt solution, wherein the metal elements contained in the metal salt solution include K and at least one of Ca, Mg, Al, Zr and Sn, and then performing a two-step calcination treatment to obtain a solid base catalyst.

2. The method for synthesizing an antioxidant using solid base catalysis according to claim 1, characterized in that: The reaction temperature of the transesterification reaction is 170-200° C., the reaction time is 5-7 h, and the reaction pressure is -0.1 MPa.

3. The method for synthesizing an antioxidant using solid base catalysis according to claim 1, characterized in that: The amount of the solid base catalyst used is 1-3% of the mass of methyl β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate.

4. The method for synthesizing an antioxidant using solid base catalysis according to any one of claims 1 to 3, characterized in that: The molar ratio of the methyl β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate to pentaerythritol is 4.5-5:

1.

5. The method for synthesizing an antioxidant using solid base catalysis according to claim 1, characterized in that: The mass concentration of the cellulose dispersed in water is 0.2-0.4%; the amount of the carboxymethyl cellulose is 20-30% of the mass of the cellulose; and the amount of the PAE is 20-30% of the mass of the cellulose.

6. The method for synthesizing an antioxidant using solid base catalysis according to claim 1 or 5, characterized in that: The amount of the polyimide used is 35-40% of the mass of the cellulose; the mass concentration of the DMF solution of the polyimide is 15-20%.

7. The method for synthesizing an antioxidant using solid base catalysis according to claim 1, characterized in that: The usage ratio of the carrier to the mixed solution is 1g:8-10mL; the usage ratio of the ammonium polyphosphate to the metal salt solution is 15-20g:1L.

8. The method for synthesizing an antioxidant using solid base catalysis according to claim 1, characterized in that: The two-step calcination treatment is: first calcination treatment at 200-300°C for 30-100 minutes, and then calcination treatment at 500-700°C for 3-6 hours.

9. The method for synthesizing an antioxidant using solid base catalysis according to claim 1, 7 or 8, characterized in that: In the metal salt solution, the concentration of K is 0.25-0.3 mol / L, the total concentration of other metal elements is 0.4-0.6 mol / L, and the concentration of a single metal element is not less than 0.1 mol / L.

10. The method for synthesizing an antioxidant using solid base catalysis according to claim 1, 7 or 8, characterized in that: The metal salt solution includes one or more aqueous solutions of metal nitrates, metal carbonates, metal hydrochlorides and metal hydroxides.

Citation Information

Patent Citations

  • A method for preparing hindered phenolic antioxidant 1010

    CN106748790B

  • Antioxidant 1010 as well as preparation method and application thereof

    CN117362174A

  • Method for continuously preparing antioxidant 1010

    CN117534565A